Kosovel in ruski literarni center konstruktivistov - Vrečko, Janez (Slavistična revija, 2003)
The paper attempts to point out Kosovel's connection with the Russian Literary Center of the Constructivists. Kosovel established critical relationship towards Černigoj, Zenithism, Futurism, he introduced kartvelianization in his kons's, "focusization", and meaning. He also defined constructivism and delineated it from constructiveness. Eventual publication of the kons's in the never realized journals Konstrukter and KONS would have had a very provocative effect. Since he could not coordinate this kind of poetry with the political responsibilities that were expected of him by the political left, which he became very close to in mid-1925, he started, simultaneously with writing kons's, "new work": integrals, which triggered an immediate response with their social and political orientation. Kons's do not belong to integrals, as has been incorrectly stated by literary criticism. If Kosovel's strategizing with his environment required that he hid his radical poetic orientation, his political position forced the government to forbid his public appearances, which so unfortunately coincided with his untimely death.
Keywords: constructivism; konstruktivizem; Kosovel, Srečko, 1904-1926; literarna avantgarda; literary avant-garde; Slovene poetry; slovenska poezija